Learning to Write Poetry Using the Expressive Writing Method for VIII Grade Students - Sendy Pratama; Any Budiarti; Aries Setia Nugraha (Global Action and Education for Society, 2026)
This research discusses the low skills in writing poetry texts in Indonesian language learning. Students still struggle with writing poetry texts because the skill of writing poetry is difficult for them due to a lack of ability to express their thoughts. The teaching methods used by Indonesian language educators have become one of the factors contributing to the low skills in writing poetry texts because they are still considered boring, as educators use quite old teaching methods that do not keep up with the times. Therefore, in this study, to determine the writer's ability to plan, implement, and evaluate Poetry Writing Learning Using the Expressive Writing Method, how is the students' ability to understand and write poetry before using the Expressive Writing Method, how is the students' ability to understand and write poetry after using the Expressive Writing Method, how is the difference in effectiveness between the experimental class and the control class in writing poetry using the Expressive Writing method as the experimental class compared to students using the regular writing method as the control class. In this study, a quantitative method with a Quasi Experimental Design was used, and the results of this research are as follows. The author was able to plan, implement, and evaluate poetry writing lessons using the Expressive Writing method, achieving very good scores. The students' ability to write poetry texts before using the Expressive Writing method had an average score of 59.35 in the experimental class, while the control class had a lower average score of 39.75. The students' ability to write poetry texts after using the Expressive Writing method had an average score of 80.90 in the experimental class and 63.35 in the control class. The improvement in students' learning outcomes in poetry writing lessons was observed in both the experimental and control classes, with an average score of 80.90 in the experimental class and 63.35 in the control class. The data shows that there was an improvement in poetry writing skills in both classes after the instruction was conducted. However, a more significant improvement occurred in the experimental class that used the expressive writing method.